The role of heuristic rules in oncological diagnosis - Słysz, Anna (Contemporary Oncology/Współczesna Onkologia, 2008)
A review of literature indicates that physicians use classical heuristics (cognitive shortcuts) in diagnosis such as: representativeness heuristic – assessing the probability that a symptom belongs to a given category (e.g. cancer) on the grounds of the degree to which it reflects prototypical features of the category; anchoring heuristic – seeking information which supports initial hypothesis and ignoring data which may be contradictory to that hypothesis. The aim of this study is to indicate the positive and negative aspects of using heuristic rules in medical diagnosis, particularly in oncological diagnosis. Currently, most cancers can be cured, but it depends on early diagnosis. The reflection on rules used in diagnosis could increase “oncological alertness” of family physicians in early oncological diagnosis.